Analysis of deviation from nominal control chart performance on short production runs - Márcio Ricardo Morelli de Meira; Pedro Carlos Oprime; Ricardo Coser Mergulhão (Production)
Abstract Paper aims This paper studies the influence of process variation on deviation from nominal control chart performance and proposes some adjustments on the control limits to make it enable on small batches. Originality Specific methods were developed to monitor small batches, mainly due to unavailability of data for precise parameters estimation, like the deviation from nominal control charts. However, Montgomery (2014) highlights some essential aspects, such as the influence of process variation on its performance. Research method The method used was mathematical modeling and computer simulation. Main findings The results validated that there is a significant influence of the process variation on the control chart performance. It has been demonstrated that small adjustments on the control limits can make it enable on lean environments. Implications for theory and practice The main contribution is demonstrating the use of deviation from nominal control chart, through the valid control limits definition regardless of the samples size.